1985
DOI: 10.1021/ma00147a007
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the propagation rate constants on the degree of polymerization in the initial stage of the anionic polymerization of methyl methacrylate in tetrahydrofuran

Abstract: Oligomers of methyl methacrylate (MMA) were prepared in a flow-tube reactor using metalloesters as initiators in THF at -46 °C. No side products were formed. The rate constants for the formation of the individual t-mers, k^, were calculated by integrating the corresponding differential equations and using optimization procedures to give a best fit to the experimentally determined conversion and molecular weight distribution (MWD). For Li+ as the counterion, is larger than the rate constant for polymerization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The concentration dependence of the k̄ p values (Table ) shows that it must be regarded as an apparent constant. For an equilibrium between unimers and dimers, it is given by eq 2, assuming that the rate constant of propagation of aggregates is much smaller than that of the nonaggregated centers, k ass ≪ α k ± , , where α = [P ± ]/[P*] is the fraction of nonassociated ion-pairs (unimers) which depends on the initiator concentration and on the equilibrium constant of aggregation, K a . For strong aggregation, which leads to eq 3…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration dependence of the k̄ p values (Table ) shows that it must be regarded as an apparent constant. For an equilibrium between unimers and dimers, it is given by eq 2, assuming that the rate constant of propagation of aggregates is much smaller than that of the nonaggregated centers, k ass ≪ α k ± , , where α = [P ± ]/[P*] is the fraction of nonassociated ion-pairs (unimers) which depends on the initiator concentration and on the equilibrium constant of aggregation, K a . For strong aggregation, which leads to eq 3…”
Section: Resultsmentioning
confidence: 99%
“…Kinetic experiments suggest that externally solvated contact ion-pairs are responsible for propagation. , Tsvetanov et al and Müller et al demonstrated that the coexistence with associated ion pairs affects the rates of polymerization of MMA using Na + and Li + as counterions in THF. Kunkel et al showed that the dynamics of the equilibrium between aggregated and nonaggregated ion pairs dominates the MWD of the resulting polymers.…”
Section: Introductionmentioning
confidence: 99%
“…in THF at -100°C, polymerization is first order in monomer and the molecular weight distribution (MWD) is very narrow (M n /M w = 1.2). While the propagation rate constant, k p , is independent of the degree of polymerization (DP > 5) [80], k p strongly depends on the concentration of the living species supporting further an equilibrium between associated and non-associated ion pairs. This situation is also confirmed by the linear dependence of the apparent polymerization rate constant of MMA at 25°C on the square root of the active species concentration [64].…”
Section: Oligomeric Chainsmentioning
confidence: 99%
“…The polymerization carried out without the presence of LiCl suggests that the reactivities of the different oligomeric species are quite different, which may, in turn explain the broad distribution of the polymer. Tsvetanov and Muller et al 20 have shown that the rate constants for the individual i-mers, (for the oligomerization of MMA initiated by methyl a-lithioisobutyrate in THF at -46 °C), depend on the degree of association of the i-mer. The rate constant drops more than 1 order of magnitude as soon as another monomer unit is added (i.e., dimeric species), indicating a decrease in reactivity and a significant increase in thermodynamic stability of the growing macroanions.…”
Section: <4>mentioning
confidence: 99%